Analysis of Busulfan in Plasma by Liquid Chromatography‐Tandem Mass Spectrometry (LC‐MS/MS). Issue 1 (29th May 2020) - Pablo, Abed; Breaud, Autumn R.; Clarke, William
Abstract: Bone marrow transplantation is used to treat particular types of cancers such as lymphoma, leukemia, and multiple myeloma. Appropriate dosing of busulfan during the preparative phase is critical for a successful allograft; if blood concentrations get too high significant liver toxicity can occur, if blood concentrations are too low, then graft‐versus‐host disease (GVHD) can develop. Busulfan monitoring in blood allows hospitals with the opportunity to provide individualized medicine to patients and improve overall patient outcome. Liquid Chromatography‐Tandem Mass Spectrometry (LC‐MS/MS) is an important analytical method for quantification of busulfan in plasma in order to optimize the dose. © 2020 Wiley Periodicals LLC. Basic Protocol : Analysis of busulfan by liquid chromatography/mass spectrometry